2020
DOI: 10.1111/joca.12310
|View full text |Cite
|
Sign up to set email alerts
|

Give mind to the gap: Measuring gender differences in financial knowledge

Abstract: Prior research consistently finds a gender gap in financial knowledge where males appear to outperform females. Despite the wealth of studies attempting to explain this gap, none have considered whether the gender gap may be a product of measurement method. This study reexamines the gender gap with item response theory (IRT) which can account for guessing behavior and differential item functioning. Survey data on 184,869 individuals from 39 countries and territories is analyzed. Results show that when IRT is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…When accounted for different nature of incorrect and "Don't know" responses, financial literacy quizzes show a considerably smaller gender gap in test scores or the absence of a significant gender difference altogether (Bucher-Koenen, Alessie, Lusardi, & van Rooij, 2016;Z. Chen & Garand, 2018;Kim & Mountain, 2019;Ooi, 2020). This may mean that, after all, women and men have comparable resources of financial knowledge and skills, while the only reason for worse results of female respondents in financial literacy tests is that women tend to admit if they do not know the correct answer, while men prefer to take a guess.…”
Section: Discussionmentioning
confidence: 99%
“…When accounted for different nature of incorrect and "Don't know" responses, financial literacy quizzes show a considerably smaller gender gap in test scores or the absence of a significant gender difference altogether (Bucher-Koenen, Alessie, Lusardi, & van Rooij, 2016;Z. Chen & Garand, 2018;Kim & Mountain, 2019;Ooi, 2020). This may mean that, after all, women and men have comparable resources of financial knowledge and skills, while the only reason for worse results of female respondents in financial literacy tests is that women tend to admit if they do not know the correct answer, while men prefer to take a guess.…”
Section: Discussionmentioning
confidence: 99%
“…Bucher-Koenen et al (2017), extending the evidence for other countries, found that only ex-Soviet countries (Russia, Romania, and East Germany) have an equal distribution of financial knowledge between sexes. However, recent literature stresses how, when asked to answer questions that measure knowledge of basic financial concepts, women are less likely than men to indicate that they do not know the answer (Bucher-Koenen et al 2017;Kim and Mountain 2019;Ooi 2020). Therefore, the lower scores of women compared to men in financial literacy surveys reflects more the differences in the genders' self-reported confidence than the gender differences in their actual level of financial knowledge.…”
Section: Factors Influencing Financial Knowledge: a Literature Reviewmentioning
confidence: 99%
“…For example, research often prioritizes gender differences (e.g. Ooi, 2020) which assumes stability of gender and again reproduces a binary understanding of gender which seems to neglect the "variations on a theme. "…”
Section: Transgender Consumer Experiencesmentioning
confidence: 99%